Accruals and Asset Valuation in Emerging Markets: Evidence from the Indonesia Stock Exchange (IDX) - Robert Jao; Marselinus Asri; Ana Mardiana (Journal of Economics and Management, 2026)
This study examines the impact of idiosyncratic risk, current operating accruals, non-current operating accruals, financial accruals, and accrual anomalies on asset pricing. A regression analysis is conducted with asset prices as the dependent variable and idiosyncratic risk, current operating accruals, non-current operating accruals, financial accruals, and accrual anomalies as independent variables. The analysis reports coefficients, standard errors, t-statistics, and significance levels for each predictor. The results show that idiosyncratic risk (β = 0.518, p < 0.001) and financial accruals (β = 0.584, p < 0.001) have a significant positive effect on asset prices. In contrast, accrual anomalies (β = -0.092, p = 0.002) have a significant negative effect. In contrast, current operating accruals and non-current operating accruals do not show significant effects. These findings indicate that idiosyncratic risk and financial accruals are key determinants of asset pricing. In contrast, accrual anomalies negatively influence asset prices, and neither current nor non-current operating accruals are significant predictors in the model. The results suggest that investors and policymakers should consider idiosyncratic risk and financial accruals when evaluating asset price performance. In contrast, the negative impact of accrual anomalies underscores the need to assess accrual-based measures in financial analysis carefully. This study emphasizes the roles of idiosyncratic risk and financial accruals in asset pricing in the Indonesian capital market. It provides insights for investors, businesses, policymakers, and academics to develop investment strategies, corporate practices, and policy decisions, particularly in emerging markets.